Investigation on biomass gasification process. (2022) - Sasikumar, C.; Sundaresan, R.; Kannan, R.; Nagaraja, M.
Abstract: Surplus availability of agricultural based biomass feedstocks has higher potential to be as one among the sources of sustainable and renewable energy. This technology has better advantages and features when compared to liquid fuels, in terms of availability, cost price and processing time span of feedstock. Rich carbonaceous biomass feed stocks are found in most biomass based raw materials which can be processed by gasification reactions. This leads to production of producer gas rich in CO, H2 and CH4, which is combustible in furnaces, boilers, combustion engines for power generation. On further gas cleaning the gas can be used for thermal applications and other applications without any hazards to the environment. The objective of present work is to investigate the gasification process. Thus Biomass based processing techniques are potential to produce renewable fuels and these techniques acts as a gate way for utilizing the surplus carbonaceous multidisciplinary Biomass feedstock's available globally.